2019
DOI: 10.1002/chem.201902886
|View full text |Cite
|
Sign up to set email alerts
|

SiO2‐Coated ZnO Nanoflakes Decorated with Ag Nanoparticles for Photocatalytic Water Oxidation

Abstract: Many strategies have been adopted to improve the photoinduced features of zinc oxide nanostructures for different applicationf ields. In this work, zinc oxide has been synthesised and decorated by plasmonicm etal nanoparticles to enhance its photocatalytic activity in the visible range. Furthermore, an insulating layer of SiO 2 has been grown between the surfaceo fzinc oxide nanoflakes and silvern anoparticles. As ynthetic procedure that allowst he accurate modulation of the insulatingl ayer thickness in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The hydrogen peroxide (H 2 O 2 ) molecules are formed as they collide with the hydrogen ions and majority charge carriers (e-). The hydrogen peroxide molecules produced can penetrate the cytoplasmic membrane, killing the bacteria [78][79][80]. The schematic illustration for the antibacterial mechanism of Co-doped ZnO-MCs is demonstrated in Figure 8.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrogen peroxide (H 2 O 2 ) molecules are formed as they collide with the hydrogen ions and majority charge carriers (e-). The hydrogen peroxide molecules produced can penetrate the cytoplasmic membrane, killing the bacteria [78][79][80]. The schematic illustration for the antibacterial mechanism of Co-doped ZnO-MCs is demonstrated in Figure 8.…”
Section: Resultsmentioning
confidence: 99%
“…Bettini et al further addressed this energy transfer mechanism in OER over a series of Ag/ZnO@SiO 2 . [ 125 ] They demonstrated that the presence of a 10 nm SiO 2 shell between Ag and ZnO could realize the best exploitation of plasmonic enhancement through PIRET. The shell of this thickness simultaneously stopped FRET from ZnO to Ag NPs and preserved PIRET from Ag to ZnO, resulting in more excited electron−hole pairs in ZnO.…”
Section: Mechanisms Of Pnp Enhancement In Apmentioning
confidence: 99%
“…As reported in the previous paragraph, the exciton is promoted by the absorption of a photon of appropriate energy, then the hole-electron photo-generated pair can be separated at the interface with an appropriate material. In a typical photo-catalytic process, an appropriate photon promotes the electron excitation from the HOMO level (or from the valence band) to the LUMO level (or to the conduction band) [120]. As well as in the case of a photovoltaic device, electron and hole migrate toward the catalyst surface to recombine or to promote a redox reaction with the compounds adsorbed on the catalyst.…”
Section: Pcs-based Supramolecular Assemblies For Photocatalyst Applicmentioning
confidence: 99%